Efeito de estratégias educacionais sobre o estigma de alunos de Medicina frente ao portador de doença mental - Alexandre de Araujo Pereira (2016)
Introduction: Medical literature has shown that significant portions of the general population, including healthcare professionals, have a highly stigmatized view of mentally ill patients, which can lead to low quality health care and difficult access to treatment. Fostering more positive attitudes toward the diminishing of this stigma among doctors may help to change this scenario. Objectives: 1) provide a transcultural validation of the Attribution Questionnaire (AQ-27) into Brazilian Portuguese, which measures the stigma related to mental illnesses, and defines its psychometric properties 2) analyze the effects of the three curricular strategies developed in the Community Mental Health Services in Belo Horizonte, Brazil, in an attempt to reduce the stigma of medical students regarding mentally ill patients, using the validated Brazilian version of the AQ-27. Methods: This study conducted a one group pre-test-post-testsurvey design developed in two stages. The AQ-27, in addition to a supplementary questionnaire to collect sociodemographic, academic, and personal experience from the medical students who work with mentally ill patients, were used. Initially, 431 students from the first to the last year of the course agreed to participate in the factorial analysis, whichvalidated the psychometric properties of the Brazilian cross-cultural adaptation of the AQ-27. Of these, 156 students were again evaluated after having participated in three different mental health curriculum rotations. In addition to multiple linear and logistic regression analyses, the data were submitted to a cluster analysis. Results: Of the 27 items that made up the scale, 16 remained unmodified; six presented changes only in the structure of the sentences composition; four required a semantic cultural adaptation, while in only one question did there arise the need to change a word to an equivalent term in Brazilian spoken Portuguese. Question 11 was removed from the questionnaire due to the low proportion of explained variance and the low factorial load, which produced the Brazilian eight factor questionnaire AQ-26B with a totalexplained variance of 68.9%. None of the sociodemographic and life history factors significantly influenced the tendency toward the students stigma, but the possibility of the choice of psychiatry as a medical career did have an impact (p = 0.042). A statistically significant reduction in the expression of the stigma was also observed when all of the mentalhealth curriculum scenarios and students were analyzed together (p < 0.001). Differences were identified when the mental health curricular strategies were analyzed considering each factor separately: Medical Practice in the Community for first-year students presented a significantreduction in the factors of Segregation (p = 0.004), Isolation (p < 0.001), Fear (p = 0.010), and especially Coercion (p = 0.004), when compared to the other educational strategies. Emergency Psychiatry Internship for final-year students showed a significant drop in the factors ofSegregation (p < 0.001), Isolation (p = 0.001), and especially Fear (p = 0.001), when compared to the other educational strategies. Psychiatry in Primary Care for fourth-year students had no positive or negative impact on attitude changes among students, with the exception of Coercion,which showed a rise after the students had studied this educational strategy (p = 0.006). The differences found were most likely due to the students degree of maturity and prior exposure throughout the entire course to the different types of patients and mental health servicesinvolved, in addition to the different class loads and teaching strategies provided. Conclusions: The Brazilian version of the questionnaire to evaluate the stigma related to the mentally ill patient (AQ-26B) demonstrated both adapted validity and internal reliability, in addition to its easy application, which can render its use feasible in Brazilian medical schools. The reduction of the stigma among medical students demands a longitudinal curricular organization, with the inclusion of educational strategies that promote the direct interaction of students with mentally ill patients, preferably provided by mental health care community services. The beginning of Med School appears to be an opportune moment in which to offer this type of activity. Moreover, the reduction in the stigma related to mental illness may well contribute to a greaterinterest on the part of the medical students in psychiatry and mental health. This experience also shows that an efficient collaboration between the University and the Brazilian Public Mental Health System can both promote mental health care and achieve educational goals.